Discovery of novel dual inhibitors of receptor tyrosine kinases EGFR and PDGFR-β related to anticancer drug resistance. (1st January 2018) - Fischer, Tim; Najjar, Abdulkarim; Totzke, Frank; Schächtele, Christoph; Sippl, Wolfgang; Ritter, Christoph; Hilgeroth, Andreas
Abstract: With ongoing resistance problems against the marketed EGFR inhibitors having a quinazoline core scaffold there is a need for the development of novel inhibitors having a modified scaffold and, thus, expected lower EGFR resistance problems. An additional problem concerning EGFR inhibitor resistance is an observed heterodimerization of EGFR with PDGFR-β that neutralises the sole inhibitor activity towards EGFR. We developed novel pyrimido[4, 5- b ]indoles with varied substitution patterns at the 4-anilino residue to evaluate their EGFR and PDGFR-β inhibiting properties. We identified dual inhibitors of both EGFR and PDGFR-β in the nanomolar range which have been initially screened in cancer cell lines to prove a benefit of both EGFR and PDGFR-β inhibition.